(3bhi GdCOhjI GdeaQOIs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS dSJ CMJGL Cf CHjf gGgfG eHdZ GdGfJaGY HeYQaI bhi GdCOhjI GdeaQOI s
(3BNQgG (B:s
(3fGbU hBNQ GdehLhO efg bhdg (B: (3` PcQ GdedM ef GdedM TF jJhdO ef eGA GdHMQ ai GdehGVY GdeYQhaI HGdedGMGJ hSfPcQ Pdc ai GdehGVY GdJi JQcR ajg GdCOhjI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs